Organizacja inteligentna w logistyce przedsiębiorstw budowlanych - Skowron-Grabowska, Beata (Smart Organization in Logistics of Building Construction Enterprises, 2005)
Value of products and services made in smart organization implemented into traditional enterprise is higher than in case of only traditional company. Logistics has basic meaning in functioning of smart organizations. Logistic solutions in such organizations indicate new direction towards higher efficiency in building construction enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 396-403